Przeszłość, przyjaźń. Dwie glosy do poematu nożyk profesora Tadeusza Różewicza - Jaworski, Marcin (Poznańskie Studia Polonistyczne. Seria Literacka, 2013)
The article is an interpretation of the eponymous long poem from Tadeusz Różewicz’s volume nożyk profesora [professor’s knife]. The first part discusses the modes modes of narration of the experience of the Holocaust. The discussion focuses on meanings of the words “memory” and “history”, on the ironic use of pastoral convention, and on the transformation of the metaphor from Cyprian Norwid’s Przeszłość [The Past]. The poem recycling from the volume zawsze fragment. recycling is an important context. The second part of the article is devoted to the friendship between Tadeusz Różewicz and Mieczysław Porębski. The description of the friends’ breakfast points out to an interpretation of their relation in the context of their wartime biography: a death camp for Porębski, and resistance fighting for Różewicz. The poet, in spite of his memory and long-time friendship with the former prisoner, presents the Holocaust as a mediated experience that is virtually inaccessible. However, in many ways he still tries to bring it closer to the reader and does not let the reader forget it.